Impact of segmental body composition on metabolic dysfunction-associated fatty liver disease in Chinese children - Hu, Meng-Yuan; Sun, Dan-Qin; Yang, Fan; Zheng, Xiao-Wei; Wu, Ning-Xi; Zhang, Hao-Yang; Yao, Xiao-Die; Zhang, Jia-Hui; Zhang, Le (Frontiers in Endocrinology, 2025)
PurposeThis study aimed to assess the relationship between regional body composition and metabolic dysfunction-associated fatty liver disease (MAFLD) in Chinese children.MethodsIn this study, 1399 children aged 7–14 years were included. Liver steatosis was assessed using the controlled attenuation parameter (CAP) measured through Fibroscan. MAFLD is defined as the presence of liver steatosis along with either overweight/obesity, prediabetes/diabetes, or at least two metabolic index abnormalities. Regression analyses were applied to assess the relationship between regional body composition and MAFLD in children. Subgroup analyses were performed based on sex and weight.ResultsThe participants had a mean age of 9 years, with 52.11% being boys. Among them, 134 (9.57%) were diagnosed with MAFLD, and 17 (1.22%) had severe fatty liver disease. We found an inverse correlation between the muscle percentage in each region and MAFLD, with the extremities demonstrating the most significant negative correlation (OR: 0.732; 95% CI: 0.634–0.844). Conversely, regional fat was positively associated with MAFLD, with the strongest correlation found in the upper limbs (OR: 3.104; 95% CI: 2.023–4.764). Subgroup analyses showed similar results.ConclusionThe decrease in regional muscle percentage, particularly in the limbs, along with the increase in regional fat percentage, especially in the upper limbs, is associated with a higher probability of developing MAFLD in prepubertal children. Additional prospective studies are needed to strengthen and validate these findings.